Cinnamomum zeylanicum Essential Oil Reduces Infestation by Alphitobius diaperinus in Poultry Litter - Testa, Manuela; Segat, Julia Corá; Baggio, Rafael Alan; Galli, Gabriela Miotto; Baretta, Carolina Riviera Duarte Maluche; Mendes, Ricardo Evandro; da Silva, Aleksandro Schafer; Baretta, Dilmar (Acta Scientiae Veterinariae, 2018)
Background: Even though insecticides are managed and the period of sanitary emptiness in poultry is respected, the elimination of Alphitobius diaperinus may not be successful. The use of essential oils of plant origin presents as a good alternative in the substitution of insecticides with synthetic molecules, since they are easy to obtain, with rapid degradation and without risk of residues for non-target organisms. The main objective of the present study was to examine whether Cinnamomum zeylanicum oil reduces Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae) infestations under experimental conditions, without causing toxicity to broilers chicks exposed to treated litter. Materials, Methods & Results: The experimental design was completely randomized, with four replications per treatment. The treatments were as follows: solvent control using the diluent Dimethyl Sulfoxide 5% (oil diluent); chemical control using 5 g/m² cypermethrin; one spray of C. zeylanicum 5% oil; and two sprays of C. zeylanicum 5% oil. Each experimental unit was infested with 150 lesser mealworm adults. At 15 days of the broiler chick’s life, blood was collected for biochemical analysis (alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, total protein, albumin, globulin, triglycerides and uric acid), and liver fragments were isolated for histopathological analysis. Using TupeTrap devices, we counted lesser mealworm 40 days after treatment. The treatments did not alter biochemical variables, and did not cause histopathological lesions in liver. The treatments with C. zeylanicum 5% oil with one and two sprays efficiently reduced lesser mealworm infestation compared with solvent control. Cypermethrin treatment had no effect. Discussion: Many of the commercial products present low effectiveness in the control of A. diaperinus, since the target organisms develop resistance to the product. In the present study, we used a higher cypermethrin dose than that recommended by the manufacturer, in order to increase efficacy in the face of possible resistance. Even so, cypermethrin did not efficiently control the organism. The effectiveness of the essential oil of C. zeylanicum tested can be attributed to the compounds found in greater quantity in the oil composition, such as cinnamaldehyde (41.27%), linalool (13.05%) and methyl eugenol (10.87%), characterized as responsible for the action of oil repellency. Monoterpenoid compounds found in essential oils extracted from plants have insecticidal action acting on the central nervous system of insects, which impairs their development, being characterized as neurotoxic compounds. The results found with the essential oil of C. zeylanicum are of great importance, since the control of A. diaperinus is not efficient because this organism has behavior that favors reinfestation in the poultry houses, such as shelter in cracks, in the draperies, below the feeders and in the soil. The biochemical analyzes of the blood can as important tools to assist in the monitoring of broilers health, in the diagnosis and treatment of diseases, and therefore the results presented are of great importance since they assist in the search for alternative methods for the control of A. diaperinus, where we can affirm that the essential oil of C. zeylanicum does not cause toxicity to broilers. Based on these results we can affirm that essential oil of Cinnamomum zeylanicum, 5%, is an effective substitute for existing commercially-available insecticides. Keywords: alternative control, cinnamon oil, insecticide, lesser mealworm.